KEPUASAN PELAYANAN PELANGGAN BERBASIS BAURAN PEMASARAN - vivid dekanawati (Universitas Sarjanawiyata Tamansiswa, 2017)
ABSTRACTÂ This study aims to examine the satisfaction of cadets from the perspective of service as an intervening based on marketing mix in Yogyakarta Maritime Academy. In this case the researcher wants to know how far the Promotion, Price and Place, Service individually or collectively affect the cadetâ€™s satisfaction. The subjects of this study are 71 cadets level III of the 3 (three) majors available at AMY namely KPN, Nautical and Teknika. In this study to test the instrument by using SPSS 17.0, and the indicator test using SmartPLS 3.0. Results of this study showed that Promotion, Price and Place simultaneously are proved together significantly influence the variable performance as 59.6 %, the remaining 40.4 % is influenced by other factors not included in the model. That is simultaneously variable promotion, price and place are proved to have an influence on the service AMY cadets. Promotion, Price, Place and Service simultaneously together influence the cadets satisfaction variables is known from the analysis hypotheses suggesting a P Value of 0.00 smaller (<) than 0.05. besides of that, if the promotion is done well, the price affordable tuition, a built in support for teaching and learning activities, the cadets will get academic services in line with expectations. Â Keywords: Promotion, Price, Place, Service, Cadets Satisfaction